AGENT-BASED MODELING ON PURCHASE DECISIONS: THE IMPACT OF SOCIAL MEDIA PHENOMENA - Siti Mariam (SEAN Institute, 2022)
Social media influencers have replaced the phenomenon of traditional influencers playing a role in digital marketing in recent years. On the other hand, academic literature needs to explain this phenomenon fully. The purpose of this study is to understand the role of social media influencers in social interaction and their implications for purchasing decisions for cosmetic products to provide an overview of companies in making business decisions using Instagram. The research employs agent-based modeling simulation (ABM), a combination of a deductive approach using the theory of planned behavior (TPB) and an inductive practice through observation. The number of posts, the number of likes and comments, the number of followers, attractiveness of influencers utilize. These parameters lead to purchasing decisions, which subsequently identify with sales figures. This study categorizes three influencers with different characteristics. The simulation results show that influencer [B] sales are the highest with repeated iterations, then influencer [A] and influencer [C] with several parameters that explain the phenomenon of social media influencers in purchasing decisions. Another discovery was that the parameter quantity of content has the most significant influence on buying decisions, followed by other parameters that also contribute significantly. To provide businesses the chance to consider these factors when selecting the right blend of social media influencers to aid product sales.